Teaching materials for Spiritual Life Skills in Counseling Services through the EDUDA Application, - Putri, Utari Dwi; Dalimunthe, Raudah Zaimah (Bisma The Journal of Counseling, 2020)
The research background of students' low spiritual life skills and the absence of online teaching materials for practicing spiritual life skills. The research objective is to produce online teaching materials for spiritual life skills that are effective in implementing student counseling services. The development research design was carried out using the ADDIE model. The research subjects of the seventh-grade students of Tunas SMP Swasta Tunas Karya Batangkuis for the 2019/2020 academic year with total of 30 students. The instruments used were questionnaires and interviews, worksheets for practicing spiritual skills. Data analysis techniques were qualitative analysis and the percentage of data analysis. Based on the validation by material experts, it was 75.71% for the category "Valid and the media experts were 86.42% for the" Valid "category. The effectiveness of teaching materials is obtained from the results of the students' practice scores of the students' training showed that 27 people had passed with an average percentage of 85% and achieved very good classification. This study stated that spiritual life skills teaching material is effective for use in counseling services to students.